The Association Between Maternal Nutritional Status During Pregnancy and Delayed Primary Tooth Eruption in Stunted Toddlers - Nabila Rizqi Amalia; Isnanto; Sri Hidayati (International Journal of Advanced Health Science and Technology, 2024)
Nutritional status during pregnancy is important for fetal development. Poor maternal nutritional status can cause delayed eruption of primary teeth in toddlers. This study was conducted because it was found that 6 out of 10 stunted toddlers who underwent dental examinations had delayed tooth eruption. This study aimed to investigate any potential associations between the pregnant women’s nutritional status and the toddler’s teeth who experience delayed eruption. This research is retrospective analytic. The total sample was 78 respondents, taken by purposive sampling method. The first visit of the Maternal and Child Health (KIA) book utilizing the Body Mass Index (BMI) to evaluate nutritional status of expectant mothers. Tooth eruption in toddlers was measured through dental examination. The analysis used was the Spearman correlation test. The findings indicated that most of mothers of toddlers during pregnancy had a nutritional status between 18.5-24.9 kg/m2 or fell into the typical group (52.6%), but from the results of dental eruption examination it was found that most of the stunted toddlers experienced delayed tooth eruption (66.7%). The conclusion of the study is that the pregnant women’s nutritional status is connected to the primary teeth’s eruption in stunted toddlers with ρ = 0.035 (p<0.05). This study has implications for the importance of paying attention to pregnant women’s dietary consumption in an attempt to avoid delayed tooth eruption in stunted toddlers.